Estudio de prefactibilidad para la instalación de una planta productora de zumo de limón envasado para el mercado local - Ballón Acuña, María Gracia (2019)
This project was born in a context in which an opportunity is identified to satisfy the need of families to have a lemon juice ready to use in various applications of the varied gastronomy. In addition, you have the necessary resources to obtain a quality product. Once the context and the reality in which the project is located are identified, we will focus on identifying who we are going to direct our product along with the strategy to be used to reach the market.